COSMOS - Results of the MOTION Demonstrator for Congestion and Incident Management Strategies in Piraeus - Kruse, Günter (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
The COSMOS project has developed and demonstrated new procedures for reducing and preventing traffic congestion in urban areas. As an example the MOTION Demonstrator in Piraeus and results of the field trials are presented. The implemented systems for intelligent urban traffic control and for route guidance do provide a significant benefit to the improvement of traffic conditions in the demonstration site of Piraeus: Travel times for the road users are improved and congestion is reduced. As an effect of the optimal urban traffic control the traffic related emissions and fuel consumption are decreasing. The results can be transfered to other cities all over the world to solve traffic problems in urban areas.